2006
DOI: 10.1002/hed.20321
|View full text |Cite
|
Sign up to set email alerts
|

Effect of immunocompromise on metastatic cutaneous squamous cell carcinoma in the parotid and neck

Abstract: Background. Our aim was to examine the effect of a compromised immune state on the outcomes in patients treated for metastatic cutaneous squamous cell carcinoma (SCC).Methods. A retrospective analysis of patients with metastatic cutaneous SCC to the parotid and neck treated at Greenlane Hospital between 1992 and 2002 was conducted. Outcomes were compared between immune-competent and immunocompromised patients. A logistic regression analysis of likely risk factors for poor outcome was done.Results. Forty-nine p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
39
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(45 citation statements)
references
References 4 publications
5
39
1
Order By: Relevance
“…Studies of immunosuppressed patients who developed HN cSCC support this, and 1 study reported that no immunosuppressed patients remained alive at 2 years post-treatment compared with 87% of patients who remained in the immunocompetent group. 26 In a large study (n ¼ 170), patients who were immunosuppressed were significantly more likely to die compared with immunocompetent patients (HR, 3.8; P<.0001). 27 Although only a minority of our patients (<10%) were immunosuppressed in the current study, this variable proved to be a powerful prognosticator.…”
Section: >3mentioning
confidence: 98%
“…Studies of immunosuppressed patients who developed HN cSCC support this, and 1 study reported that no immunosuppressed patients remained alive at 2 years post-treatment compared with 87% of patients who remained in the immunocompetent group. 26 In a large study (n ¼ 170), patients who were immunosuppressed were significantly more likely to die compared with immunocompetent patients (HR, 3.8; P<.0001). 27 Although only a minority of our patients (<10%) were immunosuppressed in the current study, this variable proved to be a powerful prognosticator.…”
Section: >3mentioning
confidence: 98%
“…Those patients had a significantly higher rate of local and/or regional relapse than did immunocompetent patients (56% vs 28%). 59 The role of chemotherapy in addition to adjuvant radiation therapy is unproven and currently awaits the maturity of randomized data, at least in the setting of non-OTRs. Although cutaneous SCC can be considered responsive to platinum-based chemotherapy, there is no convincing evidence that, in the setting of advanced or metastatic cutaneous SCC in OTRs, that chemotherapy is of significant benefit.…”
Section: Dermal (In-transit) Squamous Cell Carcinomamentioning
confidence: 99%
“…This would suggest a smaller lesion size and lesser depth of invasion associated with the development of metastatic cSCC and a significantly worse outcome compared with immunocompetent (IC) patients. In another study comparing IC and OTR patients a significant proportion of OTR had thick (>5 mm) tumors and exhibited early dermal invasion compared with IC patients [31]. Of note, patients immunosuppressed as a consequence of chronic lymphocytic leukemia (CLL) also have a similar increased risk of cutaneous SCC and poor outcome from developing metastases [32].…”
Section: Immunosuppressionmentioning
confidence: 99%